Effects of different methods and time of boron application on the nutrient concentration and uptake by wheat (Triticumaestivum L.) - Fakir, OA; Alam, MK; Alam, MJ; Jahiruddin, M; Islam, MR (Bangladesh Journal of Agricultural Research, 2018)
At present, inclusion of Boron (B) in fertilizer management practice most often determines the yield performance of crops. Methods of supply of B to plants demands more research to come to a conclusion. The effect of different methods of boron application on the nutrient concentration and uptake of wheat (Triticuma estivum L.cv. Shatabdi) was studied through a field experiment at Bangladesh Agricultural University (BAU) farm, Mymensingh during rabi season of 2012-13. The experiment was laid out in a randomized complete block design (RCBD) with six treatments and three replications. The treatments were- (i) B–control (no addition of B), (ii) soil application @ 1.5 kg ha-1, (iii) seed priming @ 0.4% boric acid solution, (iv) foliar spray @ 0.4% boric acid solution at primodia stage (37DAS), (v) foliar spray @ 0.4% boric acid solution at booting stage (55 DAS),and (vi) foliar spray at primodia stage (37DAS) and booting stages (55 DAS). Boric acid was used as a source of boron. Seed priming was done by soaking wheat seeds into 0.1% boric acid solution for 10 hours and then seeds were dried before sowing. Foliar spray of B at primodia and booting stage of crop (T6) recorded the highest B concentration of grain (19.60 μg g-1) and the control (T1) treatment performed the lowest B concentration (6.75 μg g-1). Similarly, the foliar spray of B at primodia and booting stages of crop (T6) recorded the highest B uptake by both grain and straw that was statistically identical to foliar spray of B at booting stage of crop (T5) in both cases. In view of cost-return analysis, foliar spray of B at primodia and booting stage treatment required the highest input cost but obtained the highest gross return, while control B required the lowest input cost along with lowest gross return Bangladesh J. Agril. Res. 43(3): 453-469, September 2018